The Effectiveness between Two Translation Assessment Models for English to Indonesian Translation of Undergraduate Students - Haru Deliana Dewi; Rahayu Surtiati Hidayat (Journal of Language and Literature, 2020)
Research on translation assessment on English to Indonesian translation results using two dissimilar rubrics and a quantitative approach is rarely conducted by Indonesian scholars. This present study investigated the effectiveness between two assessment models, which are very different, one using a holistic approach (the LBI Bandscale) and the other using the error analysis approach (the ATA Framework). The research has been conducted on several language pairs, including the Indonesian-English translation, but it has never been done on the English-Indonesian translation. The research aims to discover whether there is a substantial improvement using both assessment models and whether one model is more effective than the other. The study was conducted in the Introduction to Translation (DDPU) classes of the English Studies Program of the Faculty of Humanities (FIB), Universitas Indonesia (UI) for undergraduate students of Semester 6. The respondents were asked to do translation in class, and then within three weeks, their works were returned with feedback based on both models. After that, they were asked to do revisions of their translation results. The outcome of the analysis shows that there is a great improvement in the translation results because of the two assessment models, but there is no significant difference in the effectiveness between those models.